Comparing Apples to Apples or Apples to Oranges: The Role of Mental Representation in Choice Difficulty - Cho, Eunice Kim; Khan, Uzma; Dhar, Ravi (Journal of Marketing Research, 2013)
Contrary to the general view that decision difficulty is a stable characteristic of specific choice sets, the authors propose that decision difficulty depends on how the choice set is mentally represented. Comparing the difficulty associated with comparable and noncomparable choice sets, the authors find that changes in mental representation can make the same choice feel more or less difficult. They propose that the representation level influences the type of decision criterion that becomes readily available; whether this available criterion is appropriate for comparing the options in turn affects choice difficulty. Four studies demonstrate the proposed effect of representation level on the difficulty of comparable and noncomparable choices and its downstream implications for decision satisfaction.